How elite coaches' experiential knowledge might enhance empirical research on sport performance - Greenwood, D.; Davids, K.; Renshaw, I. (International Journal of Sports Science and Coaching, 2012)
In sport science, much research has been aimed at developing empirical knowledge of performance and practice. While this body of work has led to significant advances in understanding, one source of information that has been under-represented is the analysis of experiential knowledge of high-level athletes and coaches. Using the run-up task in sport as an exemplar, we were interested in understanding the relationship between the experiential knowledge of elite coaches and empirical research findings to ascertain how a combination of these knowledge sources might enrich understanding of sport performance. For this purpose, fifteen interviews were conducted with elite coaches from three sports; track and field, gymnastics, and cricket. The qualitative data showed elite coaches intuitively expressed ideas consistent with recent scientific research in their design of training and learning programs. Key ideas expressed included perception-action coupling, the effects of interacting constraints on performance, and an approach to practice which was consistent with insights from nonlinear pedagogy. The data revealed how experiential knowledge of elite coaches might be used to support and enhance empirical research processes. Specific examples include providing direction for future research, assisting in the representative design of empirical research, and highlighting limitations of some empirical research protocols and findings. The coaches' comments suggested a need for more systematic and sustained efforts to explore how experiential knowledge might enrich understanding of sport performance.